Heat transfer performance of CuCrZr/AlSi7Mg multi-material heat sinks with triply periodic minimal surface manufactured by laser powder bed fusion - Chang Liu; Yuchao Bai; Jie Chen; Guijun Bi; Mingkang Zhang; Di Wang; Mingjian Deng (Virtual and Physical Prototyping)
To achieve heat sinks with high heat transfer efficiency and lightweight, the CuCrZr/AlSi7Mg multi-material heat sinks with triply periodic minimal surface (TPMS) structure manufactured by laser powder bed fusion (LPBF) are proposed in this research. An infrared imaging camera was applied to obtain the thermal performance parameters, and the conjugate heat transfer model was combined with computational fluid dynamics to analyse the heat dissipation mechanism. The microstructure of CuCrZr/AlSi7Mg shows the formation of Al2Cu and Cu9Al4 intermetallics at the interface after LPBF, and the number of Al2Cu phases increased after direct aging heat treatment. The average heat transfer coefficient of CuCrZr/AlSi7Mg with the TPMS ratio of 3:3 (CA33) is enhanced up to 579.84 W m−2 K−1, which is higher than that of the AlSi7Mg heat sink. The simulation result reveals that the material distribution of a multi-material heat sink changes the heat transfer process, which combines the high thermal conductivity of the CuCrZr material with the lightness of the AlSi7Mg material. The special material ratio combination with the TPMS ratio of 3:3 effectively improves the heat transfer performance of the heat sink.